Analisis perkembangan usaha mikro, kecil dan menengah sebelum dan sesudah menerima pembiayaan mudharabahpada pt. bank syariah mandiri kcp pahlawan samarinda - Mashura Mashura; Sri Mintarti; Juliansyah Roy (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
This study discusses: How to differentiate business capital, sales turnover, business profits and number of workers and before using Mudharabah funds at Mandiri Syariah Bank KCP Pahlawan Samarinda.  This research is quantitative descriptive. The population of this study was the UMKM recipients of Mudharabah financing from Mandiri Syariah Bank KCP Samarinda which received 30 recipients of funds. The sampling method uses saturated Sample or census. The number of samples of this study were 30 samples. The technique of receiving data uses questionnaires and documentation to receive data about MSME business development before and after receiving Mudharabah financing. The analysis technique used in this study is the Wilcoxon sign rank test. The results of the study show that there is a difference between venture capital before and after receiving Mudharabah financing from the Mandiri Syariah Bank KCP Samarinda Heroes develop their business. There is a difference between sales turnover before and after financing receiving Mudharabah financing from Mandiri Syariah Bank KCP Samarinda Heroes need business development. There is a difference between business profits before and after receiving Mudharabah financing from Mandiri Syariah Bank KCP Samarinda Heroes improve business development. There is a difference between the number of workers before and after Mudharabah financing from Mandiri Syariah Bank KCP Pahlawan Samarinda.